PROSPECTS FOR THE DEVELOPMENT OF SMALL ENTERPRISES IN UZBEKISTAN (Intent Research Scientific Journal, 2024)
In Uzbekistan cconditions have been created to support small businesses that provide various sources of credit and other borrowed funds. At the same time, small businesses with the highest level of risk still have the opportunity to receive preferential loans from budget funds specially allocated for this by the state. Studying this problem on a regional scale allows us to formulate recommendations for improving the investment climate.